2001
DOI: 10.1074/jbc.m003719200
|View full text |Cite
|
Sign up to set email alerts
|

MEKK2 Associates with the Adapter Protein Lad/RIBP and Regulates the MEK5-BMK1/ERK5 Pathway

Abstract: The mitogen-activated protein kinase (MAPK) 1 pathways transduce various extracellular stimuli into distinct intracellular responses. The core component of such a MAPK module is a set of three sequential kinases that are evolutionarily conserved in eukaryotes from unicellular yeast to plants and animals. In mammalian cells, three distinguishable MAPK modules have been well described; they are the extracellular signalregulated kinases 1 and 2 (ERK1/2), the c-Jun N-terminal kinase (JNK), and the p38 pathways. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
141
0
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(146 citation statements)
references
References 64 publications
3
141
0
2
Order By: Relevance
“…In addition, three studies have shown that ERK5 can be activated in T cells downstream of TCR-mediated signalling [28][29][30]. It has also been reported that MEKK2, an activator of the ERK5 pathway, can interact with LAD/RIBP, an Lck-interacting adaptor protein, which is recruited to the TCR complex [18]. It has been proposed that ERK5 may control the expression of specific immediate early (IE) genes in T cells by regulating the activity of MEF2 transcription factors [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, three studies have shown that ERK5 can be activated in T cells downstream of TCR-mediated signalling [28][29][30]. It has also been reported that MEKK2, an activator of the ERK5 pathway, can interact with LAD/RIBP, an Lck-interacting adaptor protein, which is recruited to the TCR complex [18]. It has been proposed that ERK5 may control the expression of specific immediate early (IE) genes in T cells by regulating the activity of MEF2 transcription factors [9].…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is MEKK3, as mouse knockouts of MEKK3 [16] have a similar phenotype to that of ERK5 knockouts. In addition, MEKK3 has been shown to activate ERK5 in transfection experiments in Hek293 cells [17] and kinase inactive MEKK3 blocks ERK5 activation in Cos7 cells [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of other extracellular stimuli, such as epidermal growth factor and G-protein-coupled receptors, also activate ERK5 (Kato et al, 1998;Marinissen et al, 1999). Activation of ERK5 requires phosphorylation of Thr-219 and Tyr-221 residues by upstream MAPK kinase5 (MEK5), which in turn is activated by MEKK2, MEKK3, and Cot (Chao et al, 1999;Chiariello et al, 2000;Sun et al, 2001). ERK5, although activated by a similar Thr-Glu-Tyr dual phosphorylation motif as are ERK1/2 and ERK7, however, contains a unique loop-12 structure and an unusually large C-terminal nonkinase domain, which is absent in other types of MAPKs.…”
Section: Introductionmentioning
confidence: 99%
“…Some reports demonstrated that MEK5 was regulated by TNFa/JNK signal pathway (Dent et al, 2003;Yoshizumi et al, 2003). MEKK2 and MEKK3 have been demonstrated as MEK5/ERK5 direct upstream regulators (Chao et al, 1999;Chayama et al, 2001;Sun et al, 2001). It has been proven that MEK5 acts through regulating MEF2C, a member of the MEF2 transcription factor family (Kato et al, 1997).…”
Section: Introductionmentioning
confidence: 99%